Inclusive J/ψ production at midrapidity in pp collisions at √s = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; López, Jorge; Nath, Abhishek; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (The European physical journal. C, Particles and fields, 2021)
We report on the inclusive $$\text {J}/\psi $$production cross section measured at the CERN Large Hadron Collider in proton-proton collisions at a center-of-mass energy $$\sqrt{s}~=~13$$ TeV. The $$\text {J}/\psi $$mesons are reconstructed in the $$\text {e}^{+}\text {e}^{-}$$decay channel and the measurements are performed at midrapidity ($$|y|<0.9$$) in the transverse-momentum interval $$0<p_{\mathrm{T}} <40$$ GeV/$$c$$, using a minimum-bias data sample corresponding to an integrated luminosity $$L_{\text {int}} = 32.2~\text {nb}^{-1}$$and an Electromagnetic Calorimeter triggered data sample with $$L_{\text {int}} = 8.3~\mathrm {pb}^{-1}$$. The $$p_{\mathrm{T}}$$-integrated $$\text {J}/\psi $$production cross section at midrapidity, computed using the minimum-bias data sample, is $$\text {d}\sigma /\text {d}y|_{y=0} = 8.97\pm 0.24~(\text {stat})\pm 0.48~(\text {syst})\pm 0.15~(\text {lumi})~\mu \text {b}$$. An approximate logarithmic dependence with the collision energy is suggested by these results and available world data, in agreement with model predictions. The integrated and $$p_{\mathrm{T}}$$-differential measurements are compared with measurements in pp collisions at lower energies and with several recent phenomenological calculations based on the non-relativistic QCD and Color Evaporation models.